Bibliometric analysis of the use of Immunoinformatics in the production of SARS-CoV-2 vaccine prototypes - de Farias Morais, Gabriel Christian de Farias; Oliveira Pereira, Victor Leonardo; Silva de Oliveira, Claudio Bruno; Rodrigues-Neto, João Firmino; Nobre Oliveira, Jonas Ivan (Revista Cubana de Información en Ciencias de la Salud, 2024)
The COVID-19-19 pandemic’s global impact has accelerated the need for effective vaccines, challenging traditional, time-consuming, and costly vaccinology methods. Immunoinformatics emerges as a promising alternative to expedite vaccine development, thus this study aims to provide a comprehensive bibliometric analysis of its application in formulating SARS-CoV-2 vaccine prototypes. Employing VOSviewer software and data from the Web of Science database, this study conducted a bibliometric analysis. Key metrics included the global distribution of scientific publications, the most productive countries and institutions, influential authors, co-citation and co-authorship networks, and prevalent keywords in immunoinformatics research related to SARS-CoV-2 vaccines. The analysis encompassed 138 scholarly articles, with India emerging as a pivotal contributor, particularly through notable contributions from Adamas and Fakir Mohan universities. The most cited article, authored by Bhattacharya, received 226 citations, while Doytchinova was a prominent cited source, referenced in 96 of the 138 analyzed documents. The study observed substantial collaborative efforts among authors from 45 nations, with 85% of the research concentrated in just six countries. Pakistan demonstrated the highest level of international collaboration, contributing to 15/20 collaborative publications. Keywords such as ’SARS-CoV-2’, ’immunoinformatics’, and ’prediction’ were frequently encountered across most of these documents. This bibliometric analysis elucidates the primary research trends in the field and delineates the global scope and distribution of immunoinformatics studies in the realm of SARS-CoV-2 vaccine development. These findings offer a vital overview of the current landscape, guiding future research directions and potential collaborative efforts in the pursuit of effective COVID-19 vaccines.